Potential markets for new tropical forage hybrids to increase livestock system productivity and adaptability in East Africa - Junca Paredes, John Jairo; Florez, Jesus Fernando; Enciso Valencia, Karen Johanna; Hernández, Luis Miguel; Triana Ángel, Natalia; Burkart, Stefan (2024)
Dairy farming is the most prominent activity among smallholder livestock farmers in in East Africa. However, both the low quality and quantity of livestock feed limit the profitability of the sector and its ability to meet the growing demand for livestock products. The adoption of improved forages, such as forage hybrids, helps in increasing productivity and adaptability, and can thus enhance food security and income generation among the poorest rural families. The International Center for Tropical Agriculture (CIAT) has spearheaded the development of such hybrids, which, through a partnership with the seed company Grupo Papalotla from Mexico, have made inroads into over 70 countries since 2001. Currently, CIAT's breeding program is developing new hybrids of Urochloa spp. and Megathyrsus spp. tailored to the specific agroecological conditions of Sub-Saharan Africa. To identify the commercial potential of future forage hybrids for the region, we made estimates regarding the potential hectares for adoption and associated market values, particularly for interspecific Urochloa and Megathyrsus maximus hybrid lines in various East African countries. The findings reveal a potential market of 414,388 ha for new interspecific Urochloa hybrids and 528,409 ha for Megathyrsus maximus hybrids, with approximate annual values of US$73.5 and US$101.1 million, respectively. Ethiopia, Tanzania, and Kenya hold a market share of 70% for Urochloa hybrids, and South Sudan, Ethiopia, and Tanzania a 67% market share for Megathyrsus maximus. The combined potential annual seed market value for both hybrids exceeds US$170 million. These results will help different actors in decision-making related to forage seed sector development, i.e., regarding private sector investments in forage seed commercialization or public sector incentives supporting adoption processes, and thus contribute to increasing food security and sustainability in the region.